IMPLEMENTASI PEMBANGUNAN ZONA INTEGRITAS MENUJU WILAYAH BEBAS DARI KORUPSI DAN WILAYAH BIROKRASI BERSIHDAN MELAYANI DI BBWS PEMALI JUANA SEMARANG - Julia Hapsari; Hartuti Purnaweni; Budi Puspo Priyadi (Magister Administrasi Publik, FISIP, 2019)
Significantly there was an increase in the number of proposals work units that launchedthe Integrity Zone, but the increase of proposals number was not followed by the highlevel of work units breakdown towards Corruption-Free Areas and the Clean and ServingBureaucracy. Likewise, the BBWS Pemali Juana Semarang, which the value in themanagement of human resource indicators is still below the minimum value. This studyaims to analyze the implementation and factors that encourage and hinder theDevelopment of Integrity Zones Towards Corruption-Free Areas and the Clean andServing Bureaucracy in Balai Besar Wilayah Sungai Pemali Juana Semarang. Thisresearch uses descriptive qualitative approach. The results of the study show that thereare several obstacles in the implementation of policies towards WBK as follow (1) Thereare types of education and training that irrelevant to the duties and functions of the office,(2) Gaps in opportunities/rights to get education and training and other competencies,(3 ) Monev reporting has been carried out every six months, (4) The preparation of monevreports depend on the collection of SKP, (5) Short-term programs monitoring is difficult,(6) Employees pay little attention to SKP collection deadlines, (7) Employees pay lessattention to the achievements of their own performance, (8) There are employees makingmass SKP, (9) Period of individual performance measurement done every semester.